FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA KARYAWAN PADA PT. XY - Ariani, Misna; Tamara, Dwinda; Khudin Anam, Sholih; Hendrawan, Yudi; Afriliani, Ruby (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2024)
This research aims to determine the influence of the work environment, work discipline, and motivation on the job satisfaction of employees PT XY. The sampling technique in this research was total sampling with a population of 104 employees PT. XY. The data collection method was carried out by distributing questionnaires. This research uses Smart-PLS to process data. The results of this research indicate that the work environment, discipline and motivation have a positive effect on the job satisfaction of employees PT. XY. Employees feel satisfied with the supervision carried out by the leadership employees feel happy with the non-physical work environment (relationships between employees) which is getting better so that employees are able to obey the regulations set so they are able to be responsible. so that work results and achievement of motivation (security needs) are able to satisfy employees at work.